2016
DOI: 10.1007/s10803-016-2832-3
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Figures Test Performance in the Broader Autism Phenotype: A Meta-analysis

Abstract: People with autism show superior performance to controls on the Embedded Figures Test (EFT). However, studies examining the relationship between autistic-like traits and EFT performance in neurotypical individuals have yielded inconsistent findings. To examine the inconsistency, a meta-analysis was conducted of studies that (a) compared high and low Autism-Spectrum Quotient (AQ) groups, and (b) treated AQ as a continuous variable. Outcomes are consistent with superior visual search forming part of the broader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 87 publications
4
64
2
3
Order By: Relevance
“…As already noted, abnormal biases in local/global visual processing have been reported in individuals diagnosed with an ASD (e.g., Plaisted et al, 1999; Spencer et al, 2000; Pellicano et al, 2005; Bolte et al, 2007) and have also been established in neurotypical populations with higher autism-like characteristics (e.g., Grinter et al, 2009; Almeida et al, 2010; Crewther and Crewther, 2014; Crewther et al, 2015; Cribb et al, 2016). Nevertheless, although it is suggestive, as Gregory and Plaisted-Grant (2013) have argued, it cannot be assumed that the same underlying mechanism can explain a given perceptual abnormality in clinical and non-clinical groups.…”
Section: Discussionmentioning
confidence: 52%
“…As already noted, abnormal biases in local/global visual processing have been reported in individuals diagnosed with an ASD (e.g., Plaisted et al, 1999; Spencer et al, 2000; Pellicano et al, 2005; Bolte et al, 2007) and have also been established in neurotypical populations with higher autism-like characteristics (e.g., Grinter et al, 2009; Almeida et al, 2010; Crewther and Crewther, 2014; Crewther et al, 2015; Cribb et al, 2016). Nevertheless, although it is suggestive, as Gregory and Plaisted-Grant (2013) have argued, it cannot be assumed that the same underlying mechanism can explain a given perceptual abnormality in clinical and non-clinical groups.…”
Section: Discussionmentioning
confidence: 52%
“…Also, Figure-Ground visual skill scores are positively correlated with (not AQ-measured) self-reported autism-like social features (DiCriscio and Troiani 2017). Metaanalytic results also showed superior visual search within the broad autism phenotype (Cribb et al 2016). Furthermore, TD individuals with more self-reported autistic traits showed a Flanker task interference pattern similar to that of diagnosed individuals, having stronger interference at higher perceptual loads (Bayliss and Kritikos 2011;Remington et al 2009).…”
Section: Introductionmentioning
confidence: 76%
“…Instead of investigating whether someone with a certain AQ score has less problems in social functioning than someone with a somewhat higher AQ score, it is examined whether someone with an extremely low AQ score differs from someone with an extremely high score, which is not what the autism spectrum hypothesis encompasses. In case of visuospatial ability, it has already been demonstrated that in the existing literature, the superior visuospatial skills found in individuals with ASD are only evident across the broad spectrum when comparing extreme groups of TD individuals (Cribb et al 2016). This indicates that positive findings from studies using extremes do not necessarily replicate when examining a true broad spectrum consisting of a natural range of AQ scores.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations